2003
DOI: 10.1016/s0735-1097(03)00465-0
|View full text |Cite
|
Sign up to set email alerts
|

Familial atrial fibrillation is a genetically heterogeneous disorder

Abstract: Familial AF is more common than previously recognized, highlighting the importance of genetics in disease pathogenesis. In four families with AF, we have excluded linkage to chromosome 10q22-q24, establishing that at least two disease genes are responsible for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
196
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(211 citation statements)
references
References 15 publications
8
196
0
7
Order By: Relevance
“…The study subjects were clinically classified using a consistently applied set of definitions. 11,26 Briefly, 'lone AF' was defined as AF in individuals o60 years of age without hypertension or overt structural heart disease by clinical examination, ECG and echocardiography. 'Familial AF' was the lone AF in family members with X2 first-degree relatives with documented lone AF.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study subjects were clinically classified using a consistently applied set of definitions. 11,26 Briefly, 'lone AF' was defined as AF in individuals o60 years of age without hypertension or overt structural heart disease by clinical examination, ECG and echocardiography. 'Familial AF' was the lone AF in family members with X2 first-degree relatives with documented lone AF.…”
Section: Study Subjectsmentioning
confidence: 99%
“…25 Nevertheless, AF is a genetically heterogeneous disorder, and genetic defects in a significant proportion of AF patients remain to be identified. 26 In this study, we describe the identification and characterization of novel KCNA5 mutations as genetic determinants for AF.…”
Section: Introductionmentioning
confidence: 99%
“…6 A number of studies have demonstrated that AF and in particular lone AF have a substantial genetic component. [7][8][9][10][11][12][13] Oyen et al 14 have recently shown that an individual's risk of developing lone AF at a young age, increases drastically with both increasing number of relatives with lone AF and decreasing age at onset of the disease in these relatives, indicating an underlying genetic component in early onset lone AF.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that up to one-third of all patients with AF have no obvious cause and are referred to as having lone AF (23,24). The absence of other causes associated with a high incidence of family history suggest the presence of a monogenic disease.…”
Section: Discussionmentioning
confidence: 99%